Persepsi Mahasiswa Terhadap Clinical Skills Lab di Fakultas Kedokteran Universitas Muslim Indonesia Angkatan 2017 - Hidayah, Nurul; Surdam, Zulfiyah; Karsa, Nevi Sulvita; Fattah, Nurfachanti; Arfah, Arni Isnaini; Hamsah, M (Yayasan Citra Cendekia Celebes, 2023)
The curriculum is one of the keys to determining the quality of graduates. Every certain period of time the curriculum is always evaluated and then adjusted to the development of science. One form of the curriculum is clinical skills. Clinical skills are an important component in the competencies that must be mastered by a doctor. Learning clinical skills must be well integrated in the curriculum. This learning starts from the pre-clinical stage known as the skills-lab. The Skills laboratory is a place for students to obtain facilities and facilities to learn clinical skills in a laboratory situation and help ensure that all students acquire the necessary techniques and are assessed correctly. This study aims to determine the perceptions of students in class 2017 of the clinical skills lab method at the Faculty of Medicine, University. Indonesian Muslims. This research is descriptive. The number of samples used in this study amounted to 150 active students from the Faculty of Medicine at the Muslim University of Indonesia class of 2017. The results showed that students of the Faculty of Medicine of the Muslim University of Indonesia class of 2017 gave a positive response to the material, methods, facilities, readiness of students, instructors and time allocation. during the clinical skills lab. The conclusion is that the perception of students of the Faculty of Medicine, Muslim University of Indonesia, class of 2017 on clinical skills labs is good even though there are some shortcomings.